Effect of reaction temperature and flow rate of precursor on formation of multi-walled carbon nanotubes - Tee, Jia Chee; Aziz, Madzlan; Ismail, Ahmad Fauzi (Penerbit UTM Press, 2008)

(untitled)
The effect of reaction temperature and flow rate of precursor on the quantity and quality of the multi-walled carbon nanotubes (MWNTs) produced by catalytic chemical vapour deposition (CCVD) was studied. The MWNTs were grown over molecular sieve supported catalyst at 700 and 850 °C with flow rate of acetylene at 15 and 30 sccm. The effect of an in-situ heat treatment on the as-grown MWNTs at 200 °C was investigated. Thermogravimetric analysis (TGA) results show that CNT purity decreases with increasing reaction temperature, from 63.31 wt% at 700 °C to 61.68 wt% at 850 °C. However, the increase of acetylene flow rate from 15 sccm to 30 sccm has improved the yield of MWNT from 63.31 wt% to 69.28 wt%. The MWNTs grown at 850 °C with 30 sccm of acetylene show 68.23 wt% of purity, attributed to the higher acetylene flow rate. Acetylene flow rate of 30sccm produced higher purity of MWNTs whereas reaction temperature of 700 °C is more effective in generating MWNTs. The in-situ heat treatment at 200 °C gave the highest purity of MWNTs at 87.52 wt%. TEM and HRTEM images suggest that the impurities on the wall layers of MWNT yield were burn off at 200 °C. The in-situ heat treatment is able to reduce the impurities and hence yielded higher purity MWNTs.